2021
DOI: 10.1108/ejmbe-12-2020-0344
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of consumers’ price level perception and emotions towards supermarkets

Abstract: PurposeThis study aims to reveal the impact of consumers’ price sensitivity on their purchase intention within the scope of supermarkets. Besides, the study aims to examine the impact of consumers’ price sensitivity on their price perception level and emotions and the impact of consumers’ price level perception and emotions toward supermarkets on their purchase intention. It also aims to detect the mediating effects of consumers’ price level perception and emotions toward supermarkets between their price sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Trust has a positive effect on the Intention to Use (Cakici & Tekeli, 2021) stated that perception affects intention because consumers can differentiate between good and bad products. Individual perceptions of the product can describe it as a whole, thereby enabling comparison (Roth et al, 2017).…”
Section: H7mentioning
confidence: 99%
See 1 more Smart Citation
“…Trust has a positive effect on the Intention to Use (Cakici & Tekeli, 2021) stated that perception affects intention because consumers can differentiate between good and bad products. Individual perceptions of the product can describe it as a whole, thereby enabling comparison (Roth et al, 2017).…”
Section: H7mentioning
confidence: 99%
“…This finding is in line with previous research by (Dean et al, 2021), which showed a significant positive relationship between trust and intention to use. (Roth et al, 2017) and (Cakici & Tekeli, 2021) stated that higher perceptions result in lower intentions. The research revealed that when consumers have good knowledge, their perception of risk is reduced, with an increase in intentions and vice versa.…”
Section: Test the Structural Modelmentioning
confidence: 99%
“…The theoretical framework of this study integrates different research streams, such as research on retail price images (Graciola et al 2018;Hamilton and Chervev 2013;Zielke 2010), value perception (Zeithaml 1988), price fairness (Homburg et al 2005;Lu et al 2020), the role of emotions in price-related contexts (Cakici and Tekeli 2022;Peine et al 2009;Zielke 2011) and research on price as an information cue (Palma et al 2016;Völckner and Hofmann 2007). We group the model variables into cognitive (price-level perception, value for money perception, price fairness), emotional (positive, negative) and inferential (quality perception, symbolic value) dimensions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In particular, older studies with a product focus analyze the interplay between price, quality and value perception (Chang and Wildt 1994;Dodds et al 1991;Dodds 1995;Teas and Agarwal 2000;Zeithaml 1988) or antecedents and consequences of price fairness (Campbell 2007;Xia et al 2004). Older studies in retailing and services also focused on price level, quality and value (Baker et al 2002;Varki and Colgate 2001), but then started to integrate emotions as mediators between cognitive price perception and outcome variables (Cakici and Tekeli 2022;Peine et al 2009;Walsh et al 2011;Zielke 2011Zielke , 2014. Several recent studies refer to the value dimensions suggested by Sweeney and Soutar (2001), such as price, quality, emotional and social value (Diallo et al 2015;France et al 2020;Rousta and Jamshidi 2020;Slack et al 2020), but do not analyze relationships between these values.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This is particularly problematic for rapidly changing markets where new products and services are frequently introduced, or in cases where consumer preferences change significantly (Felix, 2015). Cakici & Tekeli (2022) also point out that current methods of calculating CPIs do not take into account individual differences in perceptions and preferences. Consumers may differ in their ability to detect quality differences or perceive price changes.…”
Section: Introductionmentioning
confidence: 99%